Comparative Evaluation of the Essential Oil of the New Ukrainian Lavandula angustifolia and Lavandula x intermedia Cultivars Grown on the Same Plots - Katarzyna Pokajewicz; Marietta Białoń; Liudmyla Svydenko; Nataliia Hudz; Radosław Balwierz; Dominik Marciniak; Piotr Paweł Wieczorek (Molecules, 2022)
New cultivars of lavender adapted to arid steppe conditions were developed by the Institute of Rice of Ukrainian National Academy of Agrarian Sciences (NAAS). This work is a part of the characterization process of the new cultivars. The chemical composition of the essential oil of the seven new Lavandula angustifolia and eight new Lavandula x intermedia cultivars was investigated and compared. In total, 71 different compounds were identified. Linalool and linalool acetate were the main components in both species in ranges of 26.14–57.07% and 9.08–24.45%, respectively. They were followed by terpinen-4-ol (2.16–22.44%), lavandulyl acetate (2.12–10.23%), and lavandulol (1.30–3.14) in the case of L. angustifolia and camphor (10.11–12.55%), borneol (5.49–8.71%), and eucalyptol (0.47–7.41%) in the case of L. x intermedia. The oils had a valuable terpene profile—a high linalool content and the substantial presence of lavandulol and its ester. Nevertheless, they did not comply with the industry standards, mostly due to high levels of terpinene-4-ol. Evidently, a high content of terpinen-4-ol is a characteristic feature of L. angustifolia oils bred in Ukraine. Additionally, the LA3 cultivar yielded an oil with some of the highest linalool contents reported in the literature. Statistical analysis and literature data allowed for the comparative analysis of the gathered data. MANOVA, PCA, and HCA marked caryophyllene oxide as another potential differentiating compound between studied species.